2010
DOI: 10.1176/appi.psy.51.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Chronic Back Pain Patients: Prediction of Pain Intensity and Pain Disability in Cognitive-Behavioral Treatment

Abstract: The authors concluded that reducing pain-related depression could be a central therapeutic mechanism in cognitive-behavioral treatment of chronic back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
2
26
1
Order By: Relevance
“…Anxiety and depression are common among chronic pain patients and can exacerbate pain [45-47], making mental health an important factor to address when treating these patients. BQ data showed patients in this study improved on all biopsychosocial dimensions of pain, including anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression are common among chronic pain patients and can exacerbate pain [45-47], making mental health an important factor to address when treating these patients. BQ data showed patients in this study improved on all biopsychosocial dimensions of pain, including anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that holistic approaches like osteopathy and acupuncture may have added advantages for patient groups with relatively poor mental health. However, cognitive-behavioural and stress-management techniques may need to be considered alongside these therapies for patients who have psychological barriers to recovery [45,48,49]. …”
Section: Discussionmentioning
confidence: 99%
“…4,5 Studies have shown that pain and mental health issues seldom occur in isolation but rather in combination with one another. 3,6,7 This comorbidity may result in an overall negative impact and studies indicate that individuals with chronic pain and co-occurring mental health disorders experience more intense levels of pain [8][9][10] and affective distress, 11 as well as greater disability. 9 In addition, studies have shown diminishing health-related quality of life correlating with increasing physical and mental burdens on the individual.…”
mentioning
confidence: 99%
“…3,6,7 This comorbidity may result in an overall negative impact and studies indicate that individuals with chronic pain and co-occurring mental health disorders experience more intense levels of pain [8][9][10] and affective distress, 11 as well as greater disability. 9 In addition, studies have shown diminishing health-related quality of life correlating with increasing physical and mental burdens on the individual. 9,10,12 To date, most of the published research has focused on chronic pain as an entity, and there has been limited research examining the association of neuropathic pain and psychological comorbidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation